1991
DOI: 10.1007/bf01986570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and chronic prednisolone treatment on serum zinc levels in rats with adjuvant arthritis

Abstract: Several studies in animals and humans have independently demonstrated that zinc metabolism is significantly affected either by inflammation or by glucocorticoid administration. The relative importance of these two factors was assessed in this study by the investigation of the effects on serum zinc concentrations of acute and chronic prednisolone treatments in adjuvant arthritis rats and in healthy controls animals. Acute steroid administration (3 mg/kg, i.p.) caused a rapid drop in serum zinc followed by a qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Yet this latter group showed significant additional improvement in the α -tocopherol/ γ -tocopherol ratio and plasma selenium, indicating that supplementation was efficient [26]. Zinc was also improved in the supplemented group, although the tendency for additional improvement versus placebo ( p = 0.096) was not significant after adjustment on corticosteroid use ( p = 0.390), which increases the plasma zinc level [24] and may thus have masked the effect of zinc supplementation in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet this latter group showed significant additional improvement in the α -tocopherol/ γ -tocopherol ratio and plasma selenium, indicating that supplementation was efficient [26]. Zinc was also improved in the supplemented group, although the tendency for additional improvement versus placebo ( p = 0.096) was not significant after adjustment on corticosteroid use ( p = 0.390), which increases the plasma zinc level [24] and may thus have masked the effect of zinc supplementation in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were immediately centrifuged and frozen (-80°C). Determination of CRP was run on the Cobas 8000/e502® analyzer (Roche Diagnostics, Meylan, France) using the immunoturbidimetric method [24].…”
Section: Methodsmentioning
confidence: 99%
“…Zinc level alterations have been postulated to reflect cumulative underlying immunological processes that cannot be mirrored by a disability score taken at a single time point. In particular, the absence of an acute clinical deterioration could explain the generally lower, though still within the normal range, zinc levels, which can be observed in acute clinical relapses or due to acute prednisolone therapy [ 23 , 31 ]. Despite the absence of a relationship between zinc levels and depression prevalence, recent preliminary results suggest that zinc supplementation in MS can improve psychiatric symptoms, which could be due to a zinc deficiency in both disease entities [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We consider here the possible reasons for the lack of zinc deficiency as well as differences between the zinc ranges observed in the current study and those reported elsewhere. The normal zinc range might be explained by the low rate of zinc-reducing confounding factors such as diabetes [ 12 ] or vegetarian diet [ 13 ], as well as the exclusion of pregnant patients [ 33 ] and those receiving prednisone treatment [ 31 ]. Had these factors been present in our cohort and equally distributed across the MS patients and HCs, we might expect that the inter-group difference we detected would still have been present, but that the zinc levels in the MS patient group would have fallen below the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of catabolic hormones (glucocorticoids and catecholamine) in weight loss and altered zinc homeostasis in arthritis must also be considered. [ 14 ] The present study clarified that the normal control group showed an increase in the body weight of rats while rats of the CFA group showed no weight gain till the 10 th day suggesting catabolic effects during arthritic conditions. Rhuflex-F at both dose levels depicted a significant increase in body weight compared to initial body weight recommending, anabolic effects of Rhuflex-F against Freund’s adjuvant-induced arthritis in albino rats.…”
Section: Resultsmentioning
confidence: 51%